Peredaran Narkotika Internasional Sebagai Kejahatan Luar Biasa - Budiman, Andri; Sadat, Anwar (Postulat, 2024)
Narcotics crime is an act that violates the law and is an extraordinary and organized crime. Narcotics crime is a transnational crime which is a form of crime that crosses between countries. This causes the development of narcotics crimes that occur in countries around the world that need to be eradicated completely. The development of narcotics crimes as an international crime has become something that often occurs between countries. The problems are as follows: 1. What factors influence the international circulation of narcotics? 2. How are sanctions applied for perpetrators of narcotics trafficking crimes?A crucial problem in law enforcement against narcotics crimes is the difficulty of tracking the whereabouts of narcotics criminals. This has become a significant obstacle in efforts to eradicate narcotics throughout the world, due to delays in the arrest process, network disclosure and confiscation of evidence. The target tracking process requires unpredictable time. This is because criminals often move places quickly to avoid arrest. Time limitations can be an obstacle in determining the exact whereabouts of targets. However, in the process, gradually the perpetrators of these crimes were discovered by law enforcement officers who had worked hard in the legal process.Currently, Indonesia has laws and regulations that regulate drugs, namely Law Number 5 of 1997 concerning Psychotropic Substances and Law Number 22 of 1997 concerning Narcotics which was later amended by Law Number 35 of 2009 concerning Narcotics. This is an application of Law Number 7 of 1997 concerning Ratification of the United Nations Convention Against Dark Narcotic Drugs and Psychotropic Substances 1988 (United Nations Convention About the Eradication of Dark Narcotics and Psychotropics 1988). The aim of this Convention is to promote cooperation between the Parties so that they can deal more effectively with various aspects of the illicit trafficking of narcotic drugs and psychotropic substances that have an international dimension. In carrying out their obligations under the Convention, Parties are obliged to take necessary measures, including legislative and administrative measures, in accordance with the fundamental provisions of their respective domestic legislative systems. In Indonesia itself, regulations regarding sanctions for perpetrators of narcotics crimes have been regulated in Law no. 35 of 2009 concerning Narcotics.3Comprehensive and coordinated efforts are needed from various parties, especially internal law enforcement between state institutions, which includes increasing public awareness in various countries, strengthening the capacity of law enforcement officials between countries, developing more effective and efficient law enforcement strategies, and implementing a balanced approach between law enforcement. , prevention, and rehabilitation.